Structural characterization of intermediate wheatgrass (Thinopyrum intermedium) starch. Issue 5 (2nd August 2019) - Zhong, Yingxin; Mogoginta, Juan; Gayin, Joseph; Annor, George Amponsah
Abstract: Background and objectives: Intermediate wheatgrass ( Thinopyrum intermedium, IWG), a perennial, is currently being developed into a food crop that can be used in mainstream food systems. This study focused on characterizing starches extracted from IWG kernels harvested in Roseau (IWG‐RS) and Rosemount (IWG‐RM) in Minnesota, USA, and compared with starches from Jasmine rice (JR) and hard red wheat (HRW). Thermal properties, size distribution, granule size and morphology, and the unit and internal chain profile of extracted starches were evaluated. Findings: The amylose contents of IWG‐RS and IWG‐RM were 30.7% and 30.4%, respectively. IWG starches had the lowest gelatinization temperatures. Enthalpy of gelatinization (Δ H ) of HRW was similar to that of IWG‐RM. The λ max of the starches suggests that the amylose chains and internal chains of the IWG starches were longer than those of HRW and JR. IWG‐RM has the least β‐limit dextrin and longer external chain. Unit and internal chain profiles of amylopectins between IWGs were similar. Conclusions: This study revealed that the properties of IWG starches were similar to those of wheat. Differences in some starch properties were also observed between the IWG grown at different locations. Significance and novelty: This is the first report on the unit and internal chain profile of IWG. Understanding the microstructure of starch from IWG can potentially optimize its chemical functionality.